Using Descriptive analysis to Assess the Psychosis Mental Health Effect of Intimate partner Violence in Obudu, Cross River State, Nigeria - Esther P. Archibong; Sylverster Akomaye; Egbe Tangban; Mary U. Ojong-Ejoh; Adeolu Ayodele (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The present study is aimed at using descriptive analysis to examine the mental health effect of Intimate Partner Violence on women in Obudu Local Government Area of Cross River State. Data was collected from a population of women aged 18 and above in Obudu Local Government Area, using structured questionnaire. the sample size for the study was 473, which was arrived at using the Survey Monkey Sample Size Determinant Technique. The sample for the study was arrived at using the cluster and purposive sampling technique. Descriptive analysis was used to analyze the data collected from the field. Result revealed that A significant percentage (36.41%) women suffer abuse very often with majority (41.75%) suffering both physical and emotional abuse. In the last 12 months, 22.09 percent of the women have suffered abuse from an intimate partner and 16.50 percent of the victims needed medical attention after abused. On the mental health effect of abuse on the victim only 9.47 percent of women reported not suffering from any mental health illness after being abused by an intimate partner. 34.47 percent of women suffered from depression as as result of abuse, 23.79 percent suffered from anxiety disorder, 20.63 percent suffered from mood disorder. 2.43 percent suffered from suicidal ideation, 1.70 percent suffered from post-traumatic stress disorder and 7.53 percent suffering from other mental health issues. The study conclude that intimate partner violence significantly causes mental health issues. Hence there is need for increase public awareness on the dangers of intimate partner violence by government and appropriate laws that target rural communities should be put in place to combat the problem.